Clinical Significance of Yes-Associated Protein Overexpression in Cervical Carcinoma: The Differential Effects Based on Histotypes. Issue 4 (1st May 2013) - Liu, Tianbo; Liu, Yunduo; Gao, Hongyu; Meng, Fanling; Yang, Shanshan; Lou, Ge
Abstract : Objectives: The objective of this study was to explore the prognostic values of Yes-associated protein (YAP) expression in cervical carcinoma. Methods: We compared the YAP expression of 120 samples from squamous cell carcinomas (SCCs) and 42 samples from adenocarcinomas with 22 normal cervical specimens by immunohistochemistry. The expressions of cytoplasmic and nuclear YAP were analyzed separately. Result: Yes-associated protein expression in tumors is significantly higher than the level in normal tissues. In SCCs, cytoplasmic YAP expression is associated with histologic grading, lymph node metastasis, and recurrence. Nuclear expression of YAP is absent in SCC. In adenocarcinomas, cytoplasmic YAP overexpression is associated with histologic grading, and nuclear overexpression is associated with shorter overall survival and disease-free survival. Conclusions: Our results indicate the oncogenic potential of YAP in cervical cancer and its distinct functions in SCC and adenocarcinoma.